2021
DOI: 10.1016/j.nedt.2021.104864
|View full text |Cite
|
Sign up to set email alerts
|

Examining the associations between self-care practices and psychological distress among nursing students during the COVID-19 pandemic

Abstract: There is limited research regarding the impact of self-care practices on psychological distress, specifically on nursing students during a pandemic, such as COVID-19 (Corona Virus Disease- 2019). A 10-min electronic survey was sent to nursing students at a large academic-medical center, and data from 285 student respondents were analyzed to assess psychological status, attitudes and behaviors in regards to the COVID-19 pandemic. Significant differences were found when comparing self-care practice scores by sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 30 publications
2
25
0
5
Order By: Relevance
“…Similar to depressive symptoms, the female gender [ 1 , 2 , 34 , 35 , 36 , 40 , 44 , 45 , 46 , 47 , 48 , 53 ] and year of study [ 1 , 34 , 35 , 36 , 44 , 48 , 49 , 50 , 51 , 52 ] were associated with elevated levels of anxiety among students. However, all studies using medical field students [ 1 , 11 , 54 , 55 , 56 , 57 ] reported anxiety symptoms as students were unable to complete their clinical training due to the pandemic situation.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to depressive symptoms, the female gender [ 1 , 2 , 34 , 35 , 36 , 40 , 44 , 45 , 46 , 47 , 48 , 53 ] and year of study [ 1 , 34 , 35 , 36 , 44 , 48 , 49 , 50 , 51 , 52 ] were associated with elevated levels of anxiety among students. However, all studies using medical field students [ 1 , 11 , 54 , 55 , 56 , 57 ] reported anxiety symptoms as students were unable to complete their clinical training due to the pandemic situation.…”
Section: Resultsmentioning
confidence: 99%
“…Lagging behind physical activity, one third of students reported having experienced relevant changes over the previous month in stress management, environmental exposures, and social support. Previous surveys suggest that stress was higher among respondents with sleep problems [35], substance use [20], alcohol-related problems, eating problems, and problematic internet use [36]. Moreover, those spending at least two hours outside, or less than eight hours engaged on electronic screens, were likely to experience lower levels of psychological impact [37].…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students across the world have experienced mental health problems as a result of the COVID-19 pandemic. The impact of COVID-19 goes beyond the most fundamental aspects of daily life, such as sleep patterns (Brouwer et al, 2021;Gol and Erkin, 2021). For example, a study from Turkey found that nursing students reported high levels of anxiety and fear due to COVID-19.…”
Section: Introductionmentioning
confidence: 99%